Computational coupling of moisture diffusion and mechanical deformation in polymer matrix composites. (7th April 2014) - Bailakanavar, M.; Fish, J.; Aitharaju, V.; Rodgers, W.
SUMMARY A computationally efficient multiscale–multiphysics model aimed at predicting mechanical response of thermoplastic composites subjected to different levels of moisture was developed. The mathematical model of the coupled moisture‐diffusion–mechanical‐deformation phenomenon was stated at the microscale, based on the observed experimental data, and then upscaled using a mathematical homogenization approach. A two‐way coupling between moisture diffusion and mechanical deformation was introduced by which diffusivity was enhanced by hydrostatic strain, whereas strength and stiffness were assumed to degrade because of moisture ingression, which also gives rise to swelling. The computational complexity of analyzing the two coupled physical processes at multiple scales was reduced via a model reduction scheme for multiple physical processes. The model was validated for 30% by weight filled glass fiber and carbon fiber reinforced thermoplastic composites. The moisture conditioning and uniaxial tension experiments were utilized to identify diffusion and mechanical properties at a fine scale. The identified properties were then used to validate the formulation in the three‐point bending test. Copyright © 2014 John Wiley & Sons, Ltd.